Isolation of 15 hepatitis E virus strains lacking ORF1 rearrangements from wild boar and pig organ samples and efficient replication in cell culture. Issue 5 (22nd June 2022) - Gremmel, Nele; Keuling, Oliver; Becher, Paul; Baechlein, Christine
Abstract: As a zoonotic pathogen, the hepatitis E virus (HEV) leads to numerous infections in humans with different clinical manifestations. Especially genotype 3, as causative agent of a foodborne zoonosis, is transmitted to humans by ingestion of undercooked or raw meat containing liver from HEV‐infected animals. Although the virus' prevalence and dissemination in hosts like wild boar and pig have been well characterized, HEV is greatly understudied on a molecular level and reliable cell culture models are lacking. For this reason, the present study concentrated on the isolation and subsequent characterization of porcine HEV from tissue samples derived from wild boar and domestic pigs: 222 wild boars hunted in Northern Germany were investigated for the presence of HEV RNA with a detection rate of 5.9%. Three additional HEV‐positive wild boar liver samples as well as an HEV‐positive spleen and a positive kidney from domestic pigs were included. After inoculation of positive samples onto the human hepatoma cell line PLC/PRF/5, cells were grown for several weeks. Successful isolation was confirmed by RT‐qPCR, virus passage, immunofluorescence staining and titration. Overall, 15 strains from a total of 18 RNA‐positive organ samples could be obtained and viral loads >10 9 RNA copies/ml were measured in cell culture supernatants. Accordingly, 83.3% of the HEV RNA‐positive samples contained infectious hepatitis E viral particles and therefore must be considered as a potential source for human infections. Phylogenetic analyses revealed that all isolated strains belong to genotype 3. Further genetic characterization showed a high degree of sequence variability, but no sequence insertions, in the hypervariable region within the open reading frame 1.